Comparative analysis of modern SCADA packages for production automation - Danylenko, М. М.; Sotnik, S. V. (My University, 2025)
The work reveals the main capabilities and conceptual aspects of modern SCADA packages, which are widely used to automate production processes. A detailed study of the functional characteristics of three wired systems has been carried out: InTouch, iFix, and WinCC. A comparison of their technical capabilities, architecture, supported protocols, visualization tools, security mechanisms, and economic aspects of implementation is carried out. Particular attention is paid to the analysis of potential risks and threats associated with the implementation of SCADA systems in production. Technical integration challenges, cybersecurity issues, organizational risks, and compatibility problems with existing equipment are considered. On the basis of the study, strategies for minimizing risks are proposed, and practical recommendations for choosing the optimal system depending on the specifics of the enterprise are developed. The results of the study are of practical value for enterprises planning to modernize production or introduce new automation systems. The presented materials can be used to make a reasonable choice of an SCADA system and develop an effective strategy for its implementation, taking into account the potential risks and features of a particular production.
Keywords: SCADA; review; advantages; disadvantages